Clinical Epidemiology, Risk Factors, and Control Strategies of Klebsiella pneumoniae Infection - Chang, De; Sharma, Lokesh; Dela Cruz, Charles S.; Zhang, Dong (Frontiers in Microbiology, 2021)
Klebsiella species cause infections at multiple sites, including lung, urinary tract, bloodstream, wound or surgical site, and brain. These infections are more likely to occur in people with preexisting health conditions. Klebsiella pneumoniae (K. pneumoniae) has emerged as a major pathogen of international concern due to the increasing incidences of hypervirulent and carbapenem-resistant strains. It is imperative to understand risk factors, prevention strategies, and therapeutic avenues to treat multidrug-resistant Klebsiella infections. Here we highlight the epidemiology, risk factors, and control strategies against K. pneumoniae infections to highlight the grave risk posed by this pathogen and currently available options to treat Klebsiella-associated diseases.